Parental Communication Patterns and Their Impact on Early Childhood Social Development - Ahmad Shofi Mubarok; Zulham; Nur Sholehah Dian Saputri; Kandi (Pt. Anagata Sembagi Education, 2025)
This study aims to analyze parental communication patterns and their impact on the social development of early childhood. The research approach used is descriptive qualitative, with data collection techniques through in-depth interviews, observation, and documentation. Research informants consisted of parents of early childhood children and teachers as data support. Data were analyzed using the Miles & Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results show that parental communication patterns have a significant influence on children's social development. Democratic communication patterns have been shown to support children in becoming self-confident, sociable, cooperative, and empathetic. Conversely, authoritarian communication patterns make children tend to be obedient but passive, while permissive patterns result in children who lack discipline and have difficulty sharing. Mixed communication patterns indicate inconsistent social development. In addition, nonverbal forms of communication (such as hugs, facial expressions, eye contact) play an important role in building a child's sense of security. This study emphasizes the importance of quality communication within the family to support the social development of early childhood in the digital era.